COVID-19 vaccine response and safety in patients with cancer: An overview of systematic reviews - Hong Sun; Fengjiao Bu; Ling Li; Xiuwen Zhang; Jingchao Yan; Taomin Huang (Frontiers Media S.A., 2022)
BackgroundTo date, the COVID-19 pandemic does not appear to be overcome with new variants continuously emerging. The vaccination against COVID-19 has been the trend, but there are multiple systematic reviews on COVID-19 vaccines in patients with cancer, resulting in redundant and sub-optimal systematic reviews. There are still some doubts about efficacy and safety of the COVID-19 vaccine in cancer patients.PurposeTo identify, summarize and synthesize the available evidence of systematic reviews on response and COVID-19 vaccine safety in patients with cancer.MethodsMultiple databases were searched from their inception to May 1, 2022 to fetch the relevant articles. Study quality was assessed by AMSTAR2. The protocol of this study was registered on PROSPERO (CRD42022327931).ResultsA total of 18 articles were finally included. The seroconversion rates after first dose were ranged from 37.30-54.20% in all cancers, 49.60-62.00% in solid cancers and 33.30-56.00% in hematological malignancies. The seroconversion rates after second dose were ranged from 65.30-87.70% in all cancers, 91.60-96.00% in solid cancers and 58.00-72.60% in hematological malignancies. Cancer types and types of therapy could influence vaccine response. COVID-19 vaccines were safe and well-tolerated.ConclusionsThis study suggests COVID-19 vaccine response is significantly lower in cancer patients. Number of received doses, cancer types and treatment strategies could influence response of COVID-19 vaccine in cancer patients. COVID-19 vaccines are safe and well-tolerated. Considering the emergence of several new variants of SARS-CoV-2 with potential influence on ongoing vaccination programs, there is a need for booster doses to increase the effectiveness of COVID-19 vaccines.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022327931, identifier CRD42022327931.